KAZAKHSTANI CROSS-LISTED STOCK PRICES, EFFICIENCY MARKET AND IPO - Keun Jung Lee; Assel Yerbassova (European Scientific Journal, ESJ, 2013)
As financial markets become global, foreign financial markets also become more accessible to domestic firms. It is opportunity to local firms to list their shares in a foreign exchange, in most cases a London stock exchange. But not all firms afford to list abroad due to costs associated with transaction and administrative costs. Other barriers can be the requirements, lack of transparency, legal barriers, or even distance to be listed on foreign exchange. Therefore only few Kazakhstani companies can list their shares abroad.This study emphasizes the necessity and importance of learning of main purposes of the companies to list shares abroad. Cross-listing gives opportunity to enlarge their shareholder base and make their stock available to new investors. Secondly, it increases liquidity. In a more liquid market results in higher valuation as well. Finally, by listing on foreign market is usually better in terms of investor protection and disclosure requirements.This study will be focused on an aspect of price sensitivity, and liquidity effect before and after listing abroad. Empirical studies have shown that the value of the listed firms increases in the domestic market upon the announcement of the cross-listing, and especially when the firm comes from less-developed market.